Analysis of low-temperature relaxation resonances in materials containing defects - Natsik, V.D.; Semerenko, Yu.A. (Functional Materials, 2004)
A theory has been advanced providing an adequate description of thermal-activated relaxation resonances of various physical origins in defect-containing materials. The algorithm has been proposed for processing the temperature spectra of absorption and suscep -tibility defect to determine the relaxation process activation parameters.